Unbecoming human : philosophy of animality after Deleuze - Cimatti, Felice (Plateaus., 2020)
The animality of human beings is completely unknown. Being human means to be something other than an animal, to not be an animal. Felice Cimatti, with reference to the work of Gilles Deleuze, explores what human animality looks like. He shows that becoming animal means to stop thinking of humanity as the reference point of nature and the world. It means that our value as humans has the very same value as a cloud, a rock or a spider. Drawing on a wide range of texts--from philosophical ethology to classical texts, and from continental philosophy to literature--Cimatti creates a dialogue with Flaubert, Derrida, Temple Grandin, Heidegger as well as Malaparte and Landolfi--as part of this intriguing discussion about our humanity--and our unknown animality.